Implementation of Aplikasi Manajemen Surat (AMS) Korporat to Support Communication at PT PLN (Persero) Pusharlis - Desri Aryanti; Sofiatiningsih Sofiatingsih (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
Mail management s mportant part of the administrative process. Letters are form of written communication that s carried out for the fluency of the company. t process must be managed as well as possible so the information received and submitted can be responded mmediately. Conventional mail management s currently not deal, because the process s complicated and takes a long time. Current developments have need a system to speed up the mail management process so that can be conveyed mmediately. Aplikasi Manajemen Surat Korporat s created to managed of secretarial administration. The author's purpose to carry out research at PT PLN (Persero) Pusharlis to find out the process of mail management and mplementing the Aplikasi Manajemen Surat Korporat that can support the communication process. The research used qualitative method with descriptive approach. Data collection techniques by literature studies from books and journals, interviews, and direct observations. The results, Aplikasi Manajemen Surat Koporat at PT PLN (Persero) Pusharlis has been mplemented properly with the company's standard operating procedures, the system s always updated with the current era.. ts easy use speeds up the mail management process so that information can be conveyed quickly and real time, so the communication process fluency.